Non‐Typeable Haemophilus influenzae Infection of the Junbo Mouse. Issue 1 (2nd March 2017) - Cheeseman, Michael T.; Hood, Derek W.
Abstract : Acute otitis media, inflammation of the middle ear bulla, is the most common bacterial infection in children. For one of the principal otopathogens, non‐typeable Haemophilus influenzae (NTHi), animal models allow us to investigate host‐microbial interactions relevant to the onset and progression of infection and to study treatment of middle ear disease. We have established a robust model of NTHi middle ear infection in the Junbo mouse. Intranasal inoculation with NTHi produces high rates of bulla infection and high bacterial titers in bulla fluids; bacteria can also spread down the respiratory tract to the mouse lung. An innate immune response is detected in the bulla of Junbo mice following NTHi infection, and bacteria are maintained in some ears at least up to day 56 post‐inoculation. The Junbo /NTHi infection model facilitates studies on bacterial pathogenesis and antimicrobial intervention regimens and vaccines for better treatment and prevention of NTHi middle ear infection. © 2017 by John Wiley & Sons, Inc.